Synthesis of dihydrooxazoylarylisoxazoles by conventional and under microwave conditions - Ramana, Parikibanda Venkata; Reddy, Annadi Ram (European Journal of Chemistry, 2011)
The synthesis of series of 3-aryl-4-dihydrooxazolyl-5-methyl trisubstituted isoxazoles (VI) is reported, both under thermal and microwave conditions starting from various benzaldehydes (I). Benzaldehydes undergo oximation with hydroxylamine hydrosulphate to provide oximes that upon chlorination, followed by condensation with methylacetoacetate, resulted in the formation of esters. Hydrolysis of the esters to acids followed by treatment with PCl5, resulted in the formation of acid chlorides (III) that upon reaction with hydroxyamines, gave N-β-hydoxyalkyl amides (IV). These on further reaction with SOCl2, followed by cyclization with 2 N NaOH provided oxazoline substituted isoxazoles (VI) in good yields. The conversion acid chlorides (III) to isoxazoles (VI) was also achieved by microwave irradiation in moderate to excellent yields, with shorter reaction times compared to the conventional thermal method.